Science, Scientific Literacy and Scientific Temper in the Curricular Documents - Khan, Aerum (Voices of Teachers and Teacher Educators, 2018)
Developing a scientifically literate population is a significant challenge and one of the most important objectives of Science education at school level in India as well as globally. Only a scientifically literate person can be rational, logical, and critical in her approach for making decisions and solving problems of daily life. The spirit of inquiry and the acceptance of the right to question and be questioned are fundamental to Scientific Temper. This research article attempts to review different curricular documents developed post-independence which have shown the path to the role of Science as a subject in general and scientific temper and scientific literacy in particular.